Suppression of superconductivity and enhanced critical field anisotropy in thin flakes of FeSe - Farrar, L; Bristow, M; Haghighirad, A; McCollam, A; Bending, S; Coldea, A (Springer Nature, 2020)
FeSe is a unique superconductor that can be manipulated to enhance its superconductivity using different routes while its monolayer form grown on different substrates reaches a record high temperature for a two-dimensional system. In order to understand the role played by the substrate and the reduced dimensionality on superconductivity, we examine the superconducting properties of exfoliated FeSe thin flakes by reducing the thickness from bulk down towards 9 nm. Magnetotransport measurements performed in magnetic fields up to 16T and temperatures down to 2K help to build up complete superconducting phase diagrams of different thickness flakes. While the thick flakes resemble the bulk behaviour, by reducing the thickness the superconductivity of FeSe flakes is suppressed. In the thin limit we detect signatures of a crossover towards two-dimensional behaviour from the observation of the vortex-antivortex unbinding transition and strongly enhanced anisotropy. Our study provides detailed insights into the evolution of the superconducting properties from three-dimensional bulk behaviour towards the two-dimensional limit of FeSe in the absence of a dopant substrate.